Laser line scanning thermography for surface breaking crack detection : modeling and experimental study - Puthiyaveettil, Nithin; Thomas, K Renil; Unnikrishnakurup, Sreedhar; Myrach, Philipp; Ziegler, Mathias; Balasubramaniam, Krishnan (Infrared physics & technology, 2020)
•Non-contact inspection method for crack detection in steel.•Investigation of laser line scanning thermography for fast crack detection on a stationary and moving sample.•Numerical analysis for physical explanation of laser line thermography.•Defects were incorporated as a thermally thin resistive layer (TTRL) in numerical modeling.•Algorithm for real time crack detection on moving sample. Crack detection in metallic samples at high surface temperature, hostile and hazardous environments, etc. is a challenging situation in any manufacturing industries. Most of the present NDE methods are suitable only for lower surface temperatures, especially at room temperature. In this situation, we need a fast and non-contact NDT method which can be applied even in high sample surface temperature. Laser thermography is one of the techniques having a high potential in non-contact inspection. As a preliminary investigation, in this article, we have studied the potentiality of laser line thermography in crack detection at room temperature. In laser line thermography, a continuous wave (CW) laser is used to generate a laser line, which in turn is used to scan the metal surface. The heat distribution over the sample surface is recorded by an infrared thermal (IR) camera. Two different approaches are reported in this work. Firstly, a stationary laser line source and its interaction with cracks; secondly, moving laser line source scanning over a surface with crack. When the distance between crack centre to laser line centre increases, crack detectability will decrease; and when laser power increases, crack detectability will increase. A dedicated image processing algorithm was developed to improve the detectability of the cracks. To understand the heat transfer phenomenon, a simplified 3D model for laser thermography was developed for the heat distribution during laser heating and was validated with experimental results. Defects were incorporated as a thermally thin resistive layer (TTRL) in numerical modeling, and the effect of TTRL in heat conduction is compared with experimental results.